Mohammad Hatta’s Theory in Daulat Ra’jat Magazine: Structure of Government Organization - Bahri, Syaiful; Sugiyanto, Sugiyanto (JESS (Journal of Education on Social Science); Vol 8 No 02 (2024): Agustus 2024DO - 10.24036/jess.v8i02.566, 2024)
Daulat Ra’jat was made by Mohammad Hatta from 1931 to 1934. Daulat Ra’jat gives us a concept of governmentthat Mohammad Hatta made. He made a theory about government structure to build a nation and people’s economy. This theory becomes a gap that has not been discussed by many government scientists. So, this theory must be researched in this study. The first problem formulation is what the theory about the structure of government organization is. The second problem formulation is how the structure of government organization works. This research purpose is to state the definition and the implementation ofthe structure of government organization from Mohammad Hatta’s Theory, especially according to economy perspective. This study uses library research to explore the theory. Library research is a literature study for collecting, reading, analyzing, and synthesizing the gap of theme. Primary data is from Daulat Ra’jat. Data analysis is arranged by reading data according to the theme, breaking data into some points into clusters for fulfilling the theme, synthesizing the points in cluster of them with theory used in this study and with the understanding of this researcher about the theme. The result is known that the structure of government organization is divided into two formulations: from regionals into state institutions and from organization into institution then networking between institutions. Each structure of the government must arrange governing influenced theconstitution soul, systematic networking of divisions, inside and between institutions, to implement state authority.